Use of Leader's Reading Challenge Method in Improving Reading Interest from Tourism Awareness Group (TAG) Stone Garden of West Bandung Regency through Community Reading Park (CRP) - Mardiah Mardiah (IKIP Siliwangi Bandung, 2018)
Indonesian reading culture is very low. Various ways to increase interest in reading have been done by the government. Reading Reading Movement, National Movement of Literacy of Nations has been regulated in Law no 43 of 2007 and Permendikbud No 23 year 2005. In support of the program, this research is conducted in Community Literacy Movement by Leader's Reading Challenge (LRC) method. This initiative is a form of Community Empowerment in Tourism Awareness Group (TAG) Stone Garden of West Bandung regency. The study titled Use of Leader's Reading Challenge (LRC) Method in Improving Reading Interest of Tourism Awareness Group (TAG) of West Bandung Regency through Community Reading Garden. LRC is a method used from South Australia namely Premier Reading Challenge (RRC). The method used is descriptive qualitative research. By taking observation data, interviews, questionnaires, literature studies and documentation. Initial Conditions of the people who studied have low interest in reading because many factors cause. It is very influential is the low education, low economic and less facilitated to read and no activities of literacy movements in these tourist attractions. So after the research done, it appears the increase of reading interest with the indicator, reading activities in Community Reading Park (CRP) or in the tourist spot when .The indicator of reading success is that there has been the number of books read, there has been a review made also the existence of tree literasi. Internal factor which become indicator of success is with data of result of questionnaire expressing happiness after reading book. They feel happy with LRC Literacy activity. Constraints certainly exist, which is still a lot of interesting books to read, there are still activities that encourage people to motivate reading fond. There is still much more role and support from the government and the wider community in providing funds and also providing the means to manage Community Reading Gardens and the management of tourism literacy groups.